Hubungan antara financial knowledge dan psychological well-being individu : Peran kepuasan finansial sebagai mediasi - Gemiartha, Celine Morgan; Yusuf, Keona; Njo, Anastasia; Angelie, Jesshelyn (Journal of Accounting and Digital Finance, 2024)
This study aims to analyze the effect of financial knowledge on psychological well-being, with financial satisfaction as a mediating variable. This study also uses demographic variables as controls to determine how these characteristics affect the correlations under test. This is an associative study using a purposive sampling technique on residents of Surabaya aged eighteen and above. Data were collected using a questionnaire with 121 respondents, distributed by Google Forms using WhatsApp and Instagram. The data analysis technique used multiple linear regression testing. The results of the study show that financial knowledge has a significant impact on an individual's level of financial satisfaction. Moreover, the relationship between financial satisfaction and psychological well-being is statistically significant. This study provides insights into the importance of financial knowledge in improving financial satisfaction. It discusses the implications of financial satisfaction on individuals' psychological well-being and encourages the enhancement of financial knowledge for better well-being.